Karaktersitik pembakaran droplet minyak nabati Indonesia - Winarko, W. A.; Ilminnafik, N.; Kustanto, M. N.; Perdana, D. (Universitas Mataram, 2022)
Research has been carried out on the combustion characteristics of Indonesian vegetable oil droplets. Currently, Indonesia is still developing CPO as a source of renewable fuel to replace diesel. The problem is, CPO is used as a food source so that it will affect food scarcity. Vegetable oils used in this study include CCPO, CJO, CCO and CCIO. The volume of the droplets tested was 1.25-1.31 ml and the drops were placed on a 0.1 mm type K thermocouple. The flame characteristics of the droplets tested included flame stability, ignition delay time, and temperature and flame height. The results showed that vegetable oils with higher viscosity produced more stable flames, but had low temperatures and short flames. This is because high viscosity vegetable oils produce less intense microbursts. While the ignition delays time of CCO is faster than CCPO even though it has the highest flash point. This happens because the polar nature of CCO can attract oxygen more strongly. In addition, the fatty acid content of vegetable oils also has a significant impact on fire characteristics. This is indicated by CCO which has a high content of saturated fatty acids and tends to produce a short flame.